Locating stations of public transportation vehicles for improving transit accessibility - Ziari, Hassan; Keymanesh, Mahmud R.; Khabiri, Mohammad M. (Transport, 2007)
Since transportation is one of the most complicated and the basic problem of urban life in developing countries at the present time and in various dimensions, so it is necessary to view it more scientifically‐ practically. Reducing travelling time is one way to reduce its cost .In public transportation system, it is important to determine proper travelling costs. There are various methods to determine the distances between stations. One of these methods used in England is based on logical and calculative relations in mathematics. In this paper, in addition to studying this method some changes have been made in order to reduce and modify required variables for calculation of those relations. A numerical example is designed to demonstrate the effectiveness of the method and thus developed to optimize the public transportation stop location problem. The sensitivity of the total travel time, access, speed and the effect of the parameters on the optimum stop location are analyzed and discussed. First Published Online: 27 Oct 2010